Influence of Duration of Coopetition on the Profitability of Micro and Small Enterprises: A Case of Tanzania Handicraft Industry - Mnzava, Twazihirwa Tunzo; Raphael, Gwahula; Uiso, Hawa (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The objective of this study was to investigate the influence of the duration of coopetition on the profitability of MSEs in the handicraft industry operating in Arusha, Tanzania. It employed the theories of coopetition and resource dependence as theoretical frameworks. Data collected by survey approach were quantitatively analysed using the moderated Multiple Linear Regression (MLR) model to test the hypotheses. The results demonstrated that the duration of coopetition positively and significantly influenced the MSE’s profitability before and after moderation. The resource interdependence showed a statistically significant moderating influence on strength of the relationship between the duration of coopetition and MSEs’ profitability. The results mean that more profitability is assured if the firms coopete for an extended period and that resource interdependence increases the coopetition propensity of the firms. It is recommended that longitudinal studies be done on the handicraft industry in both urban and rural setting to see if similar results would be obtained with those of cross-sectional studies. In addition, more empirical data from industry-specific MSEs other than handicrafts would substantiate the findings and would add to the coopetition theory’s knowledge and understanding.